Smear slide microscopy images of IODP Hole 389-M0097C - Webster, Jody M; Ravelo, Ana Christina; Grant, Hannah; Stewart, Margaret S; Rydzy, Marisa; Le Ber, Erwan; Allison, Nicola; Asami, Ryuji; Boston, Brian; Braga, Juan-Carlos; Brenner, Logan; Chen, Xuefei; et al. (PANGAEA, 2025)
Smear slide microscopy images of IODP Hole 389-M0097C of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs) taken during the Onshore phase of this expedition (2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen). Only one paleontology (PAL) sample taken standard wise during offshore operations was suitable for production of smear slide (389-M0097C-23R-1,70-73). For visual inspection and imaging an Olympus BX-51 stereo microscope (WKH 10x/1-2 observation tube) equipped with an Olympus DP-22 digital camera has been used. For further methodological information see methods chapter in Webster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025
Keywords: central Pacific; Coral Reef; Earth climate feedbacks; Earth history tipping points; Expedition 389; Hawaiian Drowned Reefs; Hawaiian geology; International Ocean Discovery Program (IODP); MMA Valour; Paleoclimate; sea level; volcanic